2012
DOI: 10.1088/0953-8984/24/9/095001
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of epitaxial CrxMo1−xalloy thin films

Abstract: To develop a model system containing regularly spaced misfit dislocations for studies of the radiation resistance of nanoscale defects, epitaxial thin films of Cr, Mo, and Cr(x)Mo(1-x) alloys were deposited on MgO(001) by molecular beam epitaxy. Film compositions were chosen to vary the lattice mismatch with MgO. The film structure was investigated by x-ray diffraction (XRD), Rutherford backscattering spectrometry (RBS) and scanning transmission electron microscopy (STEM). Epitaxial films with reasonably high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…It has been suggested that the crystallographic ORs between the metal film and oxide substrate, especially the bonding between the first layer metal atoms and oxide substrate layer at the interface, determine the properties of metal films22232425. Experiments show that the ORs of interfaces are largely determined by lattice mismatch2026, e.g. Nb2728, Fe2229, V3031, Ta32, and Cr20 on MgO(100) substrates.…”
mentioning
confidence: 99%
“…It has been suggested that the crystallographic ORs between the metal film and oxide substrate, especially the bonding between the first layer metal atoms and oxide substrate layer at the interface, determine the properties of metal films22232425. Experiments show that the ORs of interfaces are largely determined by lattice mismatch2026, e.g. Nb2728, Fe2229, V3031, Ta32, and Cr20 on MgO(100) substrates.…”
mentioning
confidence: 99%
“…12 However, the film still possessed some strain after deposition, as evidenced by tetragonal distortion in the lattice parameters. 10 In order to investigate the atomic distribution and extent of phase separation in the film, a compositional frequency distribution is plotted using a 200 atom bin size. 31 A binomial probability distribution is used to predict the number of bins for an ion at a particular concentration, if the distribution were statistically random.…”
Section: A Experimental Apt Resultsmentioning
confidence: 99%
“…10,11 High resolution XRD patterns were collected on a Philips X'Pert Materials Research Diffractometer (MRD). Cr 0.61 Mo 0.39 , Cr 0.77 Mo 0.23 , and Cr 0.32 V 0.68 films were chosen for the detailed APT analysis study of the extent of phase separation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have explored the effect of nanoscale defects with epitaxial thin films as a model system; the density of nanoscale misfit dislocations can be controlled by varying the film lattice parameter via alloying [9,10]. Here, we employ a similar method to explore the fundamentals of radiation damage resistance in ODS ferritic steels and nanostructured ferritic alloys by attempting to synthesize epitaxial interfaces of Fe/Y 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%